ECONOMIC VALUATION OF IRRIGATING GREEN BEANS PLANTS WITH AGRICULTURAL DRAINAGE WATER REMEDIATED WITH DHS TECHNOLOGY (Journal of Pharmaceutical Negative Results, 2022)
A field experiments were conducted at Belbeis, Sharkia governorate, to evaluate the economic impact of irrigating green bean plants with agricultural drainage water remedied with DHS technology. The obtained results showed that agricultural drainage water is reused in Egypt, where it provides about 15% of the country's irrigation needs. The costs of remediating one cubic metre of agricultural drainage water with the DHS technology totaled LE 1.03, and the amounts of remediated agricultural drainage water used to irrigate green beans grown in a soil ecosystem remediated with either microorganisms or clay minerals was reduced by 50% and 28.6% of their treasury, respectively. The net return per feddan under irrigation with remediated agricultural drainage water reached 261 percent over its counterpart irrigated with non-remediated agricultural drainage water, and the cost of each ton produced decreased under irrigation with remediated agricultural drainage water to LE 35,720. This represents 83 % more for plants grown in non-remediated soil ecosystem and irrigated with non-remediated agricultural drainage water. In comparison to its counterpart irrigated with non-remediated agricultural drainage water and grown in non-remediated soil ecosystem or in soil ecosystems remediated with either microorganisms or clay minerals respectively, the profitability of each pound spent on the production of green beans increased in soil ecosystems irrigated with remediated agricultural drainage water by 201, 99, and 126 %. For a non-remediated soil ecosystem, the return on investment per pound spent on remediating agricultural drainage water was LE 5.17; for a non-remediated soil ecosystem treated with microorganisms, LE 9.8; and for a non-remediated soil ecosystem treated with clay minerals, LE 15.58.